2016
DOI: 10.1371/journal.pone.0148100
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertension in HIV/AIDS Patients on Highly Active Antiretroviral Therapy (HAART) Compared with HAART-Naïve Patients at the Limbe Regional Hospital, Cameroon

Abstract: BackgroundHighly active antiretroviral therapy (HAART) has greatly reduced the morbidity and mortality of HIV/AIDS patients but has also been associated with increased metabolic complications and cardiovascular diseases. Data on the association between HAART and hypertension (HTN) in Africa are scarce.ObjectivesPrimarily to compare the prevalence of HTN in HIV/AIDS patients on HAART and HAART-naïve patients in Limbe, Cameroon; and secondarily to assess other socio-demographic and clinical factors associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
89
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 26 publications
(29 reference statements)
19
89
10
1
Order By: Relevance
“…Contrarily, the findings of other studies of Agrawal et al [19] indicated no disparity in the prevalence of hypertension between patients on cART and cARTnaïve patients. Furthermore, lower hypertension prevalence was observed in patients receiving cART, as reported by Dimala et al [3]. Also, 60% prevalence rate in HIV patients on cART was documented by Kanegae et al [20].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Contrarily, the findings of other studies of Agrawal et al [19] indicated no disparity in the prevalence of hypertension between patients on cART and cARTnaïve patients. Furthermore, lower hypertension prevalence was observed in patients receiving cART, as reported by Dimala et al [3]. Also, 60% prevalence rate in HIV patients on cART was documented by Kanegae et al [20].…”
Section: Discussionmentioning
confidence: 65%
“…Before the commencement of antiretroviral therapy, high blood pressures in HIV-infected subjects were frequently linked with complications including vasculopathy, renal failure, and stroke [2]. The individual cardiovascular threat, however, is influenced by myriads of risk factors such as weight gain, drug abuse, elevated blood lipids, dyslipidemia, age, diabetes, smoking and family history [3]. Cardiovascular diseases that accounted for 30% deaths worldwide are attributable to chronic and poorly controlled and uncontrolled hypertension [4].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the evidence levels, the following distribution was observed: four on level IV (10,16,20,23) ; three on level V (21)(22)24) ; and ten on level VI (11)(12)(13)(14)(15)(16)(17)(18)(19)(25)(26) .…”
Section: Resultsmentioning
confidence: 97%
“…The characterization of the 17 articles showed the year of publication varied between 2001 and 2016, with six articles published in Brazil (10)(11)(12)(13)(14)(15) , five in the United States (16)(17)(18)(19)(20) , four in European countries (21)(22)(23)(24) , one article in Cameroon (25) and one in Chile (26) . Regarding the evidence levels, the following distribution was observed: four on level IV (10,16,20,23) ; three on level V (21)(22)24) ; and ten on level VI (11)(12)(13)(14)(15)(16)(17)(18)(19)(25)(26) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation